T cell responses to the RTS,S/AS01(E) and RTS,S/AS02(D) malaria candidate vaccines administered according to different schedules to Ghanaian children. - Daniel Ansong (Public Library of Science (PLoS), 2011)
Background The Plasmodium falciparum pre-erythrocytic stage candidate vaccine RTS,S is being developed for protection of young children against malaria in sub-Saharan Africa. RTS,S formulated with the liposome based adjuvant AS01(E) or the oil-in-water based adjuvant AS02(D) induces P. falciparum circumsporozoite (CSP) antigen-specific antibody and T cell responses which have been associated with protection in the experimental malaria challenge model in adults. Methods This study was designed to evaluate the safety and immunogenicity induced over a 19 month period by three vaccination schedules (0,1-, 0,1,2- and 0,1,7-month) of RTS,S/AS01(E) and RTS,S/AS02(D) in children aged 5-17 months in two research centers in Ghana. Control Rabies vaccine using the 0,1,2-month schedule was used in one of two study sites. Results Whole blood antigen stimulation followed by intra-cellular cytokine staining showed RTS,S/AS01(E) induced CSP specific CD4 T cells producing IL-2, TNF-α, and IFN-γ. Higher T cell responses were induced by a 0,1,7-month immunization schedule as compared with a 0,1- or 0,1,2-month schedule. RTS,S/AS01(E) induced higher CD4 T cell responses as compared to RTS,S/AS02(D) when given on a 0,1,7-month schedule. Conclusions These findings support further Phase III evaluation of RTS,S/AS01(E). The role of immune effectors and immunization schedules on vaccine protection are currently under evaluation. Trial registration ClinicalTrials.gov NCT00360230.